The XVIII CIGR World Congress 2014 on Agricultural & Biosystems Engineering-Upgrading Our Quality of Life - Yingkuan, Wang (International Journal of Agricultural and Biological Engineering, 2013)
The XVIII World Congress of the International Commission of Agricultural and Biosystems Engineering (CIGR) will be held in Beijing, China in September 16-19, 2014. Preparation for the big event has been proceeding smoothly.Call for papers:The Congress will focus on the above-mentioned areas and contributions in those and the related areas are appreciated. Scientists, professors, practicing engineers, enterprises managers and students engaged in agricultural/biosystems engineering are encouraged to participate in this big event and are invited to submit paper proposals to the Congress. Detailed instructions for submitting abstracts will be in the 2 nd announcement.Preparation Office:The preparation office is located in CAAMS and the website of the Congress will be available soon. At present you may contact the Congress as follows:Prof. Lanfang ZHANGInternational Cooperation DepartmentChinese Academy of Agricultural Mechanization Sciences (CAAMS)No.1, Beishatan Deshengmen Wai, Beijing 100083, ChinaTel: 0086-10-64882358, Fax: 0086-10-64883508Email: cigrwc2014@yahoo.cn